The economics of microfinance - Armendariz, Beatriz; Morduch, Jonathan (MIT Press, 2010)
The microfinance revolution has allowed more than 150 million poor people around the world to receive small Loans without collateral, build up assets, and buy insurance. This book offers an accessible and engaging analysis of the global expansion of financial markets in poor communities.